Overlapping Mechanisms of Stress-Induced Relapse to Opioid Use Disorder and Chronic Pain: Clinical Implications - Ghitza, Udi E. (Frontiers in Psychiatry, 2016)
Over the past two decades, a steeply growing number of persons with chronic non-cancer pain have been using opioid analgesics chronically to treat it, accompanied by a markedly increased prevalence of individuals with opioid-related misuse, opioid use disorders, emergency department visits, hospitalizations, admissions to drug treatment programs, and drug overdose deaths. This opioid misuse and overdose epidemic calls for well-designed randomized-controlled clinical trials into more skillful and appropriate pain management and for developing effective analgesics which have lower abuse liability and are protective against stress induced by chronic non-cancer pain. However, incomplete knowledge regarding effective approaches to treat various types of pain has been worsened by an under-appreciation of overlapping neurobiological mechanisms of stress, stress-induced relapse to opioid use, and chronic non-cancer pain in patients presenting for care for these conditions. This insufficient knowledge base has unfortunately encouraged common prescription of conveniently-available opioid pain-relieving drugs with abuse liability, as opposed to treating underlying problems using team-based multidisciplinary, patient-centered, collaborative-care approaches for addressing pain and co-occurring stress and risk for opioid use disorder. This paper reviews recent neurobiological findings regarding overlapping mechanisms of stress-induced relapse to opioid misuse and chronic non-cancer pain, and then discusses these in the context of key outstanding evidence gaps and clinical-treatment research directions which may be pursued to fill these gaps. Such research directions, if conducted through well-designed randomized controlled trials, may substantively inform clinical practice in general medical settings on how to effectively care for patients presenting with pain-related distress and these common co-occurring conditions.